Analisis Kepuasan Konsumen Pada Pelayanan Ojek Online Dan Dampaknya Terhadap Pemberian Rating - Naisa Laila Yasri; Siti Ila Awaliah; Syamsul Hidayat (Jurnal Mahasiswa: Jurnal Ilmiah Penalaran dan Penelitian Mahasiswa, 2024)
Online motorcycle taxi (online transportation) is an online transportation service that uses an application to run it. This article discusses the analysis of consumer satisfaction with online motorcycle taxi services and its impact on rating. Rapid developments in the field of online transportation, especially in Indonesia, have created increasingly tight competition between companies providing these services, such as Gojek, Grab and Uber. The aim of this research is to identify factors that influence consumer satisfaction and order by providing ratings. The data used in this research comes from respondents who use online motorcycle taxi services, especially Gojek, Grab and Uber. The results of the analysis show that service quality is a factor that influences consumer satisfaction and rating. Previous research has also shown that consumer satisfaction has a positive and significant influence on consumer loyalty. In addition, this article also identifies several problems faced by online motorcycle taxi drivers, such as excessive working hours and lack of job security and protection. This article provides a better understanding of the importance of consumer satisfaction in the online transportation industry and provides recommendations for companies- service provider companies in improving service quality and paying attention to consumer needs in order to maintain their market share.